Implementasi Fuzzy Logic Dalam Menentukan Kondisi Rumah Tidak Layak Huni (RTLH) Dan Rumah Layak Huni (RLH) - Stephen; Kwok Tan Riyo; Kee, Ferdynand; Az, Nazilatul; Nadya Mayla Putri Rahmadani (Telcomatics, 2024)
The Use of Fuzzy Logic to Select Between Uninhabitable House Conditions (RTLH) and Livable Houses (RLH) is focused on the running system as the subject of research. Starting with identifying issues, literature studies, data collection, problem analysis, fuzzy logic needs analysis, data analysis (variable classification), fuzzy system design, testing with the Sugeno method, testing with MATLAB software. The results of the program testing are in accordance with the diagram below. We get results that match the input member values ​​of the established rules. If the roof is good enough, the floor is not good enough, and the walls are very good, then the house is not livable. The fuzzy control system involves three fuzzy inputs and one fuzzy output. Each of these variables has a membership function that groups values ​​into four categories: Less Good, Fairly Good, Good, and Very Good. There are 64 fuzzy rules that link the combination of roof, floor, and wall conditions with the category of house eligibility. This fuzzy control system is then utilized to manage these rules. By simulating the conditions of the roof, floor, and walls, the system will calculate the value of the house's eligibility. If the eligibility value exceeds 50, the house is considered suitable for habitation; on the other hand, if the value is below 50, the house is considered uninhabitable. Therefore, this system can assess whether a house is livable or not based on its physical condition, providing a more objective and consistent decision than traditional assessment methods. This application shows that the use of fuzzy logic can be effective in assessing the livability of a house, especially in evaluating the subjective and complex physical condition of a house.